Thriving in the gig economy: flexibility, innovation, and opportunity / Amariah Hanum Hussin, Jamil Mohamed Sapari, and Musliha Musman - Hussin, Amariah Hanum; Mohamed Sapari, Jamil; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The gig economy, a labour market characterized by short-term contracts and freelance work, is a realm of empowerment. It liberates individuals, allowing them to be their own boss and opt for short-term or contract work over permanent jobs. This freedom empowers workers to set their own targets, work independently, and receive direct payments for their services without waiting until the end of the month. Examples include Grab drivers, delivery personnel, photographers, and sellers of goods like headscarves or desserts on platforms like TikTok and Shopee. One compelling story is that of a “makcik,” around 60 years old, who decided to join Maxim after retiring because she felt bored at home. Her journey is a testament to the vast opportunities in the gig economy, dependent on the individual's effort and willingness to work. She found high demand for her services, as female clients preferred a female driver, and she often received extra tips from clients who appreciated her nanny-like presence. Her story is a beacon of inspiration for those considering the gig economy, showing that age is not a barrier and that there are always new opportunities to explore.